Moisture-absorbing quick-drying fabric and preparation method thereof
By combining the composite nanomaterial with modified cotton fibers, the modified cotton fiber is formed, and a hydrophobic copolymer layer and hydrophilic silk fibroprotein film are formed on its surface, the problem that existing moisture-absorbing and quick-drying clothing is difficult to effectively discharge sweat during exercise, and the excellent moisture-absorbing and fast-drying performance, long-lasting antibacterial properties and other functional effects of the fabric are achieved.
Patent Information
- Application Number
- CN202510281160.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing moisture-absorbing and quick-drying clothing is difficult to effectively discharge sweat during exercise, resulting in a sticky or stuffy feeling, and lack of antibacterial performance.
Compound nanomaterials are combined with modified cotton fibers, and the modified cotton fiber is formed by depositing aaminolated composite nanomaterials on the oxidized cotton fibers, and a hydrophobic copolymer layer and hydrophilic silk fibroin film are formed on its surface, improving the moisture-wicking and antibacterial properties of the fabric.
It achieves excellent moisture absorption and quick-drying performance of the fabric, long-lasting antibacterial properties, anti-mites, mosquito repellent and cool effects, and improves the comfort and safety of sportswear.
Smart Images

Figure CN119773311A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of layered materials, in particular to a moisture-absorbing quick-drying fabric and a preparation method thereof. Background Art
[0002] With the development of science and technology and the continuous improvement of people's quality of life, people's requirements for clothing have undergone a series of changes, from having clothes to having good-looking clothes to now requiring a variety of functional clothing, such as windproof clothing, UV protection clothing, sportswear, etc. In recent years, as people's enthusiasm for participating in sports has increased, the comfort requirements for clothes during exercise have also increased, especially moisture-absorbing and quick-drying clothing has gradually attracted people's attention and recognition. In the state of exercise, the human body is prone to sweating. When the sweat on the skin contacts the clothing, the sweat will be absorbed by the fabric. If the fabric cannot quickly discharge the sweat or evaporate it into the air, the fabric will be in a wet state, and when it contacts the skin, it will make the human body feel sticky or stuffy, and it is easy to breed bacteria. Therefore, the research and development of fabrics with moisture-absorbing and quick-drying properties has a broad market and is also a major research hotspot in the current scientific research field. For example, Chinese patent CN118048708B provides a moisture-absorbing and quick-drying polyester fiber and fabric, which is made by polycondensation and spinning of dibasic acid and modified diol monomers, but the antibacterial property of the moisture-absorbing and quick-drying polyester fiber needs to be improved. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for preparing a moisture-absorbing and quick-drying fabric, comprising the following steps: Step 1: treating the composite nanomaterial with 3-aminopropyltriethoxysilane to obtain an amino composite nanomaterial; oxidizing cotton fiber with sodium periodate to obtain oxidized cotton fiber, depositing the amino composite nanomaterial on the oxidized cotton fiber to obtain modified cotton fiber; spinning the modified cotton fiber into yarn, knitting, and obtaining an inner layer fabric; The method for preparing the composite nanomaterial comprises the following steps: Step A1, preparing boron nitride nanorods using boric acid and melamine as raw materials, and then treating them to obtain oxygen-doped boron nitride nanorods; Step A2, growing nano cuprous oxide on oxygen-doped boron nitride nanorods, and then chlorine-doping the nano cuprous oxide to obtain a modified cuprous oxide / boron nitride nano material; depositing nano zinc oxide on the modified cuprous oxide / boron nitride nano material to obtain a composite nano material; Step 2: Copolymerizing dodecyl methacrylate and glycidyl methacrylate to obtain a binary copolymer, and applying the binary copolymer to one side of the inner layer fabric to obtain a hydrophobic treated inner layer fabric; Step 3, eugenol is modified by bis(2-mercaptoethyl) ether to obtain modified eugenol; the modified eugenol reacts with allyl glycidyl ether to obtain a modifier; the silk fibroin is modified by the modifier to obtain modified silk fibroin; the modified silk fibroin is electrostatically spun on the side of the inner layer fabric that has been treated with hydrophobicity but not treated with hydrophobicity to form a silk fibroin film to obtain a modified inner layer fabric; Step 4: melt spinning the polyester masterbatch to obtain shaped polyester fibers; spinning the shaped polyester fibers into yarns, knitting, and obtaining surface fabrics; soaking the surface fabrics in a sodium hydroxide aqueous solution and a 3-mercaptopropyltriethoxysilane treatment solution to obtain functionalized modified surface fabrics; treating the functionalized modified surface fabrics with a hydrophilic finishing solution containing a modified hydrophilic finishing agent to obtain modified surface fabrics; The modified surface layer fabric is laminated with one side of the silk fibroin film in the modified inner layer fabric, and the layers are aligned and compounded to obtain a moisture-absorbing and quick-drying fabric.
[0004] Preferably, in step 1, the weight of the inner layer fabric is 60-80 g / m 2 ; The British count of yarn spun from modified cotton fiber is 30-50.
[0005] Furthermore, in step 1, the method for preparing the composite nanomaterial comprises the following steps: Step A1, adding boric acid to deionized water, and stirring at 40-50°C for 10-30 minutes, then adding 0.02g / mL melamine aqueous dispersion, stirring and reacting at 40-50°C for 5.5-6.5h, and drying the reaction mixture at 65-75°C to obtain a boron nitride precursor; sintering the boron nitride precursor at 1000-1200°C for 100-150min in a nitrogen atmosphere to obtain boron nitride nanorods; wherein the mass ratio of boric acid, deionized water, and melamine aqueous dispersion is (3.7-7.4):(40-80):(60-120); Adding boron nitride nanorods to a sodium hydroxide aqueous solution with a concentration of 5 mol / L, stirring at 75-85° C. for 5.5-6.5 hours, centrifuging, washing, and drying to obtain oxygen-doped boron nitride nanorods; wherein the amount ratio of the boron nitride nanorods to the sodium hydroxide aqueous solution is (1-2) g: (250-500) mL; In the above process, boric acid and melamine are used as precursors to prepare rod-shaped boron nitride nanorods. The rod-shaped structure has a suitable aspect ratio and can form a better thermal conductive network. The boron nitride nanorods are then treated, and oxygen atoms tend to attack the electron-deficient boron positions in the BN-O structure. Hydroxyl groups are introduced on the surface of the boron nitride nanorods through oxygen doping, thereby improving its interfacial compatibility with cotton fibers and providing anchoring sites for the growth of cuprous oxide. Step A2, adding oxygen-doped boron nitride nanorods and copper nitrate into deionized water, ultrasonically dispersing for 20-40 minutes, then stirring at room temperature for 1-2 hours, adding hydrazine hydrate, precipitating for 1-2 hours, filtering, washing, and drying to obtain cuprous oxide / boron nitride nanomaterials; wherein the mass ratio of oxygen-doped boron nitride nanorods, copper nitrate, deionized water, and hydrazine hydrate is (4-5):(1.7-3.4):(80-100):(1.1-1.9); The cuprous oxide / boron nitride nanomaterial is mixed with sodium chloride in a mass ratio of (3-5):(0.5-0.9), ground at room temperature for 10-20 minutes, washed with water for 3-5 times, and dried to obtain a modified cuprous oxide / boron nitride nanomaterial; The modified cuprous oxide / boron nitride nanomaterial is mixed with a 0.5 mol / L zinc chloride aqueous solution at a dosage ratio of (0.6-1.2) g: (100-300) mL, reacted in an ultrasonic microwave co-reactor for 100-150 min, filtered, washed, and dried to obtain a composite nanomaterial; In the above process, oxygen-doped boron nitride nanorods are used as a matrix, copper nitrate is used as a metal precursor, nano-cuprous oxide is in-situ grown on the oxygen-doped boron nitride nanorods through the reduction of hydrazine hydrate, and then the cuprous oxide is doped with chlorine, so that the band gap of the chlorine-doped nano-cuprous oxide is reduced and the visible light absorptivity is enhanced, so that the chlorine-doped nano-cuprous oxide has better antibacterial ability under light conditions; further, nano-zinc oxide with antibacterial effect is grown on the surface of the modified cuprous oxide / boron nitride nanomaterial, and while synergistically antibacterial, the presence of nano-zinc oxide can also prevent cuprous oxide from contacting with air, enhance the stability of cuprous oxide, and exert a better antibacterial effect.
[0006] Preferably, in step 1, the preparation method of the modified cotton fiber is: The composite nanomaterial is dispersed in toluene, subjected to ultrasonic treatment for 100-150 minutes, and then 3-aminopropyltriethoxysilane is added, and refluxed at 110-130° C. for 12-16 hours, and purified to obtain an amino composite nanomaterial; wherein the mass ratio of the composite nanomaterial, toluene, and 3-aminopropyltriethoxysilane is (3-6):(100-200):(0.3-0.9); The cotton fiber is added to a sodium periodate aqueous solution with a concentration of 0.2 g / mL, with a bath ratio of 1:(40-50), and the mixture is stirred in a nitrogen atmosphere at a temperature of 33-37° C. and oxidized for 1.5-2.5 hours in the dark, filtered, washed, and dried to obtain oxidized cotton fiber; The aminated composite nanomaterial is added into deionized water, ultrasonically treated for 20-40 minutes, and then stirred for 1-2 hours to obtain a cotton fiber treatment solution with a concentration of 0.1-0.3 g / mL; the oxidized cotton fiber is added into the cotton fiber treatment solution with a bath ratio of 1:(40-50), stirred for reaction at 45-55° C. for 10-15 hours, filtered, washed, and dried to obtain modified cotton fiber; In the above process, the composite nanomaterial is treated with 3-aminopropyltriethoxysilane to introduce abundant amino groups on its surface; the cotton fiber is treated with sodium periodate to convert part of the hydroxyl groups on its surface into aldehyde groups, and the aldehyde groups are combined with the amino groups in the amino composite nanomaterial through Schiff base reaction, and the composite nanomaterial is grafted on the cotton fiber in the form of chemical bonds, thereby obtaining modified cotton fiber; due to the presence of oxygen-doped boron nitride nanorods, chlorine-doped cuprous oxide and zinc oxide nanoparticles in the composite nanomaterial, the inner layer fabric has good moisture absorption and breathability of cotton fabric, skin-friendliness, and also has lasting antibacterial and cooling effects.
[0007] Preferably, in step 2, the preparation method of the hydrophobic treated inner layer fabric is: Add dodecyl methacrylate, glycidyl methacrylate and azobisisobutyronitrile to 1,4-dioxane, and carry out polymerization reaction at 75-85°C for 1.5-2.5 hours in a nitrogen atmosphere. After the reaction, filter, wash and dry to obtain a binary copolymer; wherein the mass ratio of dodecyl methacrylate, glycidyl methacrylate, azobisisobutyronitrile and 1,4-dioxane is (30.5-61.1):(27.3-51.2):(0.3-0.9):(40-60); The binary copolymer is added to 1,4-dioxane to obtain a hydrophobic finishing liquid with a mass fraction of 10-15%; the hydrophobic finishing liquid is atomized and then applied to one side of the inner layer fabric for 20-40 seconds, the resulting fabric is heated at 175-185° C. for 3-8 minutes, then rinsed with 1,4-dioxane for 3-5 times, and dried to obtain a hydrophobic treated inner layer fabric; In the above process, dodecyl methacrylate and glycidyl methacrylate are copolymerized to form a binary copolymer having a hydrophobic alkyl chain and an epoxy group. The binary copolymer is applied to one side of the cotton fabric by a "mist polymerization" technique. The epoxy group in the binary copolymer can react with the amino group in the water of the amino composite nanomaterial on the surface of the modified cotton fiber. The binary copolymer is covered on one side of the inner fabric by forming a chemical bond, thereby strengthening the connection strength between the binary copolymer and the inner fabric, and realizing a hydrophobic treatment on one side of the inner fabric. Preferably, in step 3, the preparation method of the modified inner layer fabric is: Mix eugenol, bis(2-mercaptoethyl) ether and N,N-dimethylformamide, stir and react at room temperature for 3.5-4.5 hours, and after the reaction, rotary evaporate to obtain modified eugenol; wherein the mass ratio of eugenol, bis(2-mercaptoethyl) ether and N,N-dimethylformamide is (8.2-16.4):(6.9-13.8):(150-200); Modified eugenol, allyl glycidyl ether and N,N-dimethylformamide are mixed, stirred and reacted at room temperature for 5-7 hours, and after the reaction is completed, rotary evaporation is performed to obtain a modifier; wherein the mass ratio of modified eugenol, allyl glycidyl ether and N,N-dimethylformamide is (10-15):(5.7-11.4):(100-120); At 55-65° C., add silk fibroin to a lithium bromide aqueous solution with a concentration of 9.3 mol / L, stir for 40-80 min, then add a modifier, stir and react at 55-65° C. for 5.5-6.5 h, dialyze for 5-7 days after the reaction, replace distilled water 3 times a day during the dialysis period, freeze-dry the product after the dialysis to obtain modified silk fibroin and store it at 4° C. for future use; wherein the mass ratio of silk fibroin, lithium bromide aqueous solution and modifier is (20-40):(150-200):(9-21); The modified silk fibroin and formic acid are mixed to obtain a spinning solution with a mass fraction of 13-15%, and then electrospinning is performed on the side of the hydrophobic treated inner layer fabric that is not hydrophobic treated to obtain a modified inner layer fabric; wherein the electrospinning conditions are: an applied voltage of 12-14 kV, a receiving distance of 13-15 cm, a propulsion rate of 0.0020-0.003 mm / s, an electrospinning needle of 21-22 G, a temperature of 25-35 ° C, and a humidity of 30-50%; In the above process, eugenol is a natural substance with antibacterial, anti-mite and mosquito repellent effects. Bis(2-mercaptoethyl) ether contains two thiol groups, and the thiol group at one end is first combined with the carbon-carbon double bond of eugenol through a thiol-ene reaction, and the thiol group at the other end is then combined with the carbon-carbon double bond of allyl glycidyl ether to obtain a modifier containing an epoxy group and a eugenol structure; the silk fibroin is then modified with the modifier, and the epoxy group in the modifier is combined with the amino group of the silk fibroin to obtain a modified silk fibroin with antibacterial, anti-mite and mosquito repellent properties; the modified silk fibroin is then electrospun to form a hydrophilic silk fibroin membrane on the inner layer, and the micropores and nanopores of the silk fibroin membrane are significantly smaller than those of the cotton fabric, and due to the hydrophobicity difference on both sides of the inner layer fabric, unidirectional moisture transport is achieved, which is conducive to the discharge of sweat and improves the perspiration and quick-drying performance of the inner layer fabric.
[0008] Preferably, in step 4, the spinning temperature of the polyester masterbatch is 270-290°C; the British count of the yarn spun from the shaped polyester fiber is 30-50; the gram weight of the surface fabric is 80-100g / m 2 .
[0009] Preferably, in step 4, the preparation method of the modified surface layer fabric is: The surface fabric is immersed in a sodium hydroxide aqueous solution with a concentration of 200 g / L and a bath ratio of 1:(40-60), and after stirring and soaking for 20-40 minutes at 75-85° C., the surface fabric is taken out, washed, and dried to obtain a pretreated surface fabric; the pretreated surface fabric is immersed in a 3-mercaptopropyltriethoxysilane treatment solution with a bath ratio of 1:(40-60), and after stirring and soaking for 20-40 minutes at room temperature, the surface fabric is taken out, washed, and dried to obtain a functionalized modified surface fabric; wherein the mass fraction of 3-mercaptopropyltriethoxysilane in the 3-mercaptopropyltriethoxysilane treatment solution is 4-6%, and the solvent is obtained by mixing ethanol and distilled water in a volume ratio of 4:1; Adding a modified hydrophilic finishing agent to deionized water to obtain a hydrophilic finishing liquid, immersing the functionalized modified surface fabric in the hydrophilic finishing liquid at a bath ratio of 1:(25-35), taking it out after treatment under ultraviolet radiation, pre-baking it at 95-105°C for 2-4 minutes, and then baking it at 155-165°C for 70-90 seconds to obtain a modified surface fabric; wherein, first, the amount of the modified hydrophilic finishing agent is 1-3% owf; ultraviolet radiation conditions: ultraviolet light power 450-550W, irradiation distance 8-12cm, irradiation time 25-35min; In the above process, the polyester masterbatch is made into a special-shaped polyester fiber, which is endowed with better moisture absorption, air permeability and quick-drying properties, and is then made into a surface fabric; the surface fabric is soaked in a sodium hydroxide aqueous solution to generate many hydroxyl groups on the surface of the polyester fabric, and then treated with 3-mercaptopropyltriethoxysilane to introduce mercapto groups on the surface of the surface fabric; and then under ultraviolet light irradiation, the mercapto groups react with the carbon-carbon double bonds in the modified hydrophilic finishing agent to graft the modified hydrophilic finishing agent onto the surface fabric.
[0010] Furthermore, in the step 4, the preparation method of the modified hydrophilic finishing agent is: Step B1, 2-mercapto-1,4-phthalic acid, ethylene glycol, p-toluenesulfonic acid and N,N-dimethylformamide are mixed, heated to 120-130° C. in a nitrogen atmosphere, stirred and reacted for 4-5 hours, and after the reaction is completed, purified to obtain an intermediate product; wherein the mass ratio of 2-mercapto-1,4-phthalic acid, ethylene glycol, p-toluenesulfonic acid and N,N-dimethylformamide is (9.9-19.8):(3.1-6.2):(0.5-0.9):(100-120); The intermediate product, 2-acrylamide-2-methylpropane sulfone and deionized water are mixed, stirred and reacted at room temperature for 5-7 hours. After the reaction is completed, the solvent is evaporated to obtain a hydrophilic compound; wherein the mass ratio of the intermediate product, 2-acrylamide-2-methylpropane sulfone and deionized water is (2.9-5.8):(2.1-4.2):(100-120); Dissolve triethanolamine in N,N-dimethylformamide, and add 1-bromobutane dropwise, heat to 65-75°C, stir and react for 11-13h, and rotary evaporate to obtain a quaternary ammonium salt compound; wherein the mass ratio of triethanolamine, 1-bromobutane and N,N-dimethylformamide is (7.5-15):(8.2-16.4):(30-50); A hydrophilic compound, a quaternary ammonium salt compound, polyethylene glycol 400, and antimony trioxide are mixed, heated to 200-240° C. in a nitrogen atmosphere, the temperature is kept constant and the pressure is reduced to 0.001-0.02 MPa, and the reaction is continued for 2.5-5 hours to obtain a hydrophilic finishing agent; wherein the mass ratio of the hydrophilic compound, the quaternary ammonium salt compound, polyethylene glycol 400, and antimony trioxide is (3.6-8.6):(10-20):(6.5-13):(0.1-0.3); In the above process, 2-mercapto-1,4-phthalic acid and ethylene glycol are combined through an esterification reaction to obtain an intermediate product containing two hydroxyl groups and a thiol group, and the thiol group in the intermediate product reacts with the double bond of 2-acrylamide-2-methylpropane sulfone to obtain a hydrophilic compound containing two hydroxyl groups and a hydrophilic sulfonic acid group; triethanolamine and 1-bromobutane undergo a quaternization reaction to generate a hydrophilic and antibacterial quaternary ammonium salt compound; further, the hydrophilic compound, the quaternary ammonium salt compound and the hydrophilic polyethylene glycol 400 are dehydrated and condensed to obtain a hydrophilic finishing agent; Step B2, mixing a hydrophilic finishing agent, isocyanoethyl methacrylate, and N,N-dimethylformamide, adding dibutyltin dilaurate, stirring and reacting at 75-85° C. for 4.5-5.5 hours, and rotary evaporating to obtain a modified hydrophilic finishing agent; wherein the mass ratio of the hydrophilic finishing agent, isocyanoethyl methacrylate, N,N-dimethylformamide, and dibutyltin dilaurate is (10.1-20.8):(7.8-15.6):(150-200):(0.08-0.15); In the above process, the hydroxyl group in the hydrophilic finishing agent reacts with the isocyanate group in isocyanoethyl methacrylate to introduce a carbon-carbon double bond into the hydrophilic finishing agent.
[0011] The moisture-absorbing and quick-drying fabric is prepared by adopting the method for preparing the moisture-absorbing and quick-drying fabric.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The moisture-absorbing and quick-drying fabric of the invention is obtained by compounding a modified inner layer fabric and a modified surface layer fabric, and has not only excellent moisture-absorbing and quick-drying performance and lasting antibacterial performance, but also good anti-mite and mosquito repellent performance and a cool feeling.
[0013] The modified inner layer fabric of the present invention is prepared with modified cotton fiber as raw material. The cotton fiber has excellent moisture absorption, air permeability and skin affinity. After modification, the composite nanomaterial of the present invention is grafted on the surface of the cotton fiber. Due to the synergistic effect of oxygen-doped boron nitride nanorods, chlorine-doped cuprous oxide and zinc oxide nanoparticles in the composite nanomaterial, the inner layer fabric has long-lasting and excellent antibacterial and cooling effects. Further, the inner layer fabric is modified to form a hydrophobic binary copolymer layer and a hydrophilic modified silk fibroin membrane on both sides thereof. Due to the hydrophobicity gap formed on both sides of the inner layer fabric and the fact that the micropores and nanopores of the silk fibroin membrane are significantly smaller than those of the cotton fabric, unidirectional moisture transport is achieved, which is conducive to the discharge of sweat, solves the problem of poor moisture conduction and moisture discharge performance of cotton fiber, and improves the perspiration and quick-drying performance of the inner layer fabric. In addition, due to the introduction of the eugenol structure in the modified silk fibroin, the antibacterial performance of the inner layer fabric is improved, and it has certain anti-mite and mosquito repellent effects.
[0014] The surface fabric of the invention is made of heterosexual polyester fiber with good moisture absorption, air permeability and quick drying properties as raw materials. The surface fabric is treated to introduce a thiol functional group on its surface so that it is combined with a modified hydrophilic finishing agent in the form of a chemical bond, thereby improving the adhesion strength of the modified hydrophilic finishing agent, solving the problem of poor hydrophilic moisture absorption of the polyester fiber, and improving the moisture absorption and perspiration performance of the surface fabric. In addition, the presence of the antibacterial quaternary ammonium salt group in the modified hydrophilic finishing agent of the invention improves the antibacterial performance of the surface fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a process flow chart of the preparation method of the moisture-absorbing and quick-drying fabric of the present invention; Figure 2 It is a comparison chart of the antibacterial rate test of Escherichia coli and Staphylococcus aureus of the moisture-absorbing and quick-drying fabrics prepared in Examples 3-5 of the present invention and Comparative Examples 4-9; Figure 3 It is a comparison chart of water absorption test of the moisture-absorbing and quick-drying fabrics prepared in Examples 3-5 of the present invention and Comparative Examples 4-9; Figure 4 It is a comparison chart of the moisture permeability test of the moisture-absorbing and quick-drying fabrics prepared in Examples 3-5 of the present invention and Comparative Examples 4-9. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0017] This embodiment discloses a method for preparing a composite nanomaterial, comprising the following steps: Step A1, adding 5.6g of boric acid to 60g of deionized water, and stirring at 45°C for 20min, then adding 90g of 0.02g / mL melamine aqueous dispersion, stirring at 45°C for 6h, and drying the reaction mixture at 70°C to obtain a boron nitride precursor; sintering the boron nitride precursor at 1100°C for 120min in a nitrogen atmosphere to obtain boron nitride nanorods; 1.5 g of boron nitride nanorods were added to 375 mL of a 5 mol / L sodium hydroxide aqueous solution, stirred at 80°C for 6 h, centrifuged, and the resulting precipitate was washed alternately with deionized water and ethanol until the pH of the washing solution was neutral, and dried at 60°C for 25 h to obtain oxygen-doped boron nitride nanorods; Step A2, adding 4.5g of oxygen-doped boron nitride nanorods and 2.6g of copper nitrate to 90g of deionized water, ultrasonically dispersing for 30min, then stirring at room temperature for 1.5h, adding 1.5g of hydrazine hydrate, precipitating for 1.5h, filtering, washing the obtained filter residue with deionized water for 4 times, freeze-drying to obtain cuprous oxide / boron nitride nanomaterial; mixing 4g of cuprous oxide / boron nitride nanomaterial with 0.7g of sodium chloride, grinding at room temperature for 15min, washing with water 4 times, and drying to obtain modified cuprous oxide / boron nitride nanomaterial; 0.9 g of modified cuprous oxide / boron nitride nanomaterial was added to 200 mL of 0.5 mol / L zinc chloride aqueous solution, reacted in an ultrasonic microwave co-reactor for 120 min, filtered, washed, and dried to obtain a composite nanomaterial. Example 2
[0018] This embodiment discloses a method for preparing a modified hydrophilic finishing agent, comprising the following steps: Step B1, 14.9 g of 2-mercapto-1,4-phthalic acid, 4.7 g of ethylene glycol, 0.7 g of p-toluenesulfonic acid and 110 g of N,N-dimethylformamide were mixed, heated to 125 ° C. in a nitrogen atmosphere, stirred and reacted for 4.5 hours. After the reaction was completed, the crude product was refined with a saturated sodium bicarbonate aqueous solution and deionized water, and the residual water and solvent were removed by rotary evaporation to obtain an intermediate product; 4.4 g of the intermediate product, 3.2 g of 2-acrylamide-2-methylpropane sulfonate, and 110 g of deionized water were mixed and stirred at room temperature for 6 h. After the reaction was completed, the solvent was evaporated to obtain a hydrophilic compound; 11.3 g of triethanolamine was dissolved in 40 g of N,N-dimethylformamide, and 12.3 g of 1-bromobutane was added dropwise, and the mixture was heated to 70° C. and stirred for 12 h. The solvent and excess 1-bromobutane were removed by rotary evaporation to obtain a quaternary ammonium salt compound; 6.1 g of the intermediate product, 15 g of the quaternary ammonium salt compound, 9.7 g of polyethylene glycol 400, and 0.2 g of antimony trioxide were mixed, heated to 220° C. in a nitrogen atmosphere, the temperature was kept constant and the pressure was reduced to 0.001 MPa, and the reaction was continued for 3.5 h to obtain a hydrophilic finishing agent; Step B2: 15.5 g of a hydrophilic finishing agent, 11.7 g of isocyanoethyl methacrylate, and 180 g of N,N-dimethylformamide were mixed, 0.12 g of dibutyltin dilaurate was added as a catalyst, the mixture was stirred and reacted at 80° C. for 5 h, and the solvent was removed by rotary evaporation to obtain a modified hydrophilic finishing agent. Example 3
[0019] This embodiment discloses a method for preparing a moisture-absorbing and quick-drying fabric, comprising the following steps: Step 1: Disperse 3 g of the composite nanomaterial in 100 g of toluene, perform ultrasonic treatment for 100 min, add 0.3 g of 3-aminopropyltriethoxysilane, reflux at 110° C. for 16 h, centrifuge, wash, and dry to obtain an amino composite nanomaterial; The cotton fiber was added to a sodium periodate aqueous solution with a concentration of 0.2 g / mL at a bath ratio of 1:40, and the mixture was kept at 33°C in a nitrogen atmosphere for 2.5 h under stirring and protected from light for oxidation. The solid product was filtered and washed with ethanol and deionized water for 3 times each, and dried in vacuo at 35°C to obtain oxidized cotton fiber. The aminated composite nanomaterial was added into deionized water, ultrasonically treated for 20 minutes, and stirred for 1 hour to obtain a cotton fiber treatment solution with a concentration of 0.1 g / mL; the oxidized cotton fiber was added into the cotton fiber treatment solution with a bath ratio of 1:40, stirred and reacted at 45°C for 15 hours, and filtered, and the obtained solid product was washed with ethanol and deionized water for 3 times respectively, and vacuum dried at 35°C to obtain modified cotton fiber; The modified cotton fiber was spun into a yarn with a British count of 30, and knitted to obtain a yarn with a gram weight of 60 g / m 2 The inner fabric; Step 2: Add 30.5 g of dodecyl methacrylate, 27.3 g of glycidyl methacrylate, and 0.3 g of azobisisobutyronitrile to 40 g of 1,4-dioxane, and polymerize at 75° C. for 2.5 h in a nitrogen atmosphere. After the reaction is completed, filter the residue, wash it with 1,4-dioxane and ethanol twice each, and dry it to obtain a binary copolymer; The binary copolymer is added to 1,4-dioxane to obtain a hydrophobic finishing liquid with a mass fraction of 10%; the hydrophobic finishing liquid is atomized with an air compression atomizer, and then applied to one side of the inner layer fabric for 20 seconds, the resulting fabric is heated at 175°C for 8 minutes, and then rinsed with 1,4-dioxane for 3-5 times, and dried to obtain a hydrophobic treated inner layer fabric; Step 3: 8.2 g of eugenol, 6.9 g of bis(2-mercaptoethyl) ether, and 150 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 3.5 h. After the reaction was completed, the solvent was removed by rotary evaporation at 80° C. to obtain modified eugenol; 10 g of modified eugenol, 5.7 g of allyl glycidyl ether, and 100 g of N,N-dimethylformamide were mixed and stirred at room temperature for 5 h. After the reaction was completed, the solvent and excess allyl glycidyl ether were removed by rotary evaporation at 80 ° C to obtain a modifier; At 55°C, 20g of silk fibroin was added to 150g of 9.3mol / L lithium bromide aqueous solution, stirred for 40min, and then 9g of modifier was added, stirred and reacted at 55°C for 6.5h. After the reaction, it was dialyzed for 5 days, during which distilled water was replaced 3 times a day. After the dialysis, the product was freeze-dried to obtain modified silk fibroin and stored at 4°C for future use. The modified silk fibroin and formic acid were mixed to obtain a spinning solution with a mass fraction of 13%, and then electrospinning was performed on the side of the hydrophobic treated inner layer fabric that was not hydrophobic treated to obtain the modified inner layer fabric; wherein, the electrospinning conditions were: an applied voltage of 12 kV, a receiving distance of 13 cm, a propulsion rate of 0.0020 mm / s, an electrospinning needle of 21 G, a temperature of 25 ° C, and a humidity of 30%; Step 4: melt the polyester masterbatch and spin it at 270°C using a spinneret with a cross-shaped hole to obtain a shaped polyester fiber; spin the shaped polyester fiber into a yarn with a British count of 30, and knit it to obtain a yarn with a gram weight of 80g / m 2 Surface fabric; The surface fabric is immersed in a sodium hydroxide aqueous solution with a concentration of 200 g / L and a bath ratio of 1:40, and after being stirred and immersed at 75°C for 40 minutes, it is taken out, washed, and dried to obtain a pretreated surface fabric; the pretreated surface fabric is immersed in a 3-mercaptopropyltriethoxysilane treatment solution with a bath ratio of 1:40, and after being stirred and immersed at room temperature for 20 minutes, it is taken out, washed, and dried to obtain a functionalized modified surface fabric; wherein the mass fraction of 3-mercaptopropyltriethoxysilane in the 3-mercaptopropyltriethoxysilane treatment solution is 4%, and the solvent is obtained by mixing ethanol and distilled water in a volume ratio of 4:1; The modified hydrophilic finishing agent is added to deionized water to obtain a hydrophilic finishing liquid, and the functionalized modified surface fabric is immersed in the hydrophilic finishing liquid with a bath ratio of 1:25. After being treated under ultraviolet light radiation, the fabric is taken out, pre-baked at 95°C for 4 minutes, and then baked at 155°C for 90 seconds to obtain a modified surface fabric; wherein, first, the amount of the modified hydrophilic finishing agent is 1% owf; the ultraviolet light radiation conditions are: ultraviolet light power 450W, irradiation distance 8cm, irradiation time 35min; The modified surface layer fabric is laminated with one side of the silk fibroin film in the modified inner layer fabric, and the layers are aligned and compounded to obtain a moisture-absorbing and quick-drying fabric. Example 4
[0020] This embodiment discloses a method for preparing a moisture-absorbing and quick-drying fabric, comprising the following steps: Step 1: Disperse 6 g of the composite nanomaterial in 200 g of toluene, perform ultrasonic treatment for 150 min, add 0.9 g of 3-aminopropyltriethoxysilane, reflux for 12 h at 130° C., centrifuge, wash, and dry to obtain an amino composite nanomaterial; The cotton fiber was added to a sodium periodate aqueous solution with a concentration of 0.2 g / mL at a bath ratio of 1:50, and the mixture was kept at 37°C in a nitrogen atmosphere under stirring and oxidized for 1.5 h in the dark. The solid product was filtered and washed 5 times with ethanol and deionized water respectively, and dried in vacuum at 40°C to obtain oxidized cotton fiber. The aminated composite nanomaterial was added to deionized water, ultrasonically treated for 40 minutes, and stirred for 2 hours to obtain a cotton fiber treatment solution with a concentration of 0.3 g / mL; the oxidized cotton fiber was added to the cotton fiber treatment solution at a bath ratio of 1:50, stirred and reacted at 55°C for 10 hours, and filtered, and the obtained solid product was washed with ethanol and deionized water for 5 times each, and vacuum dried at 40°C to obtain modified cotton fiber; The modified cotton fiber was spun into a yarn with a British count of 50 and knitted to obtain a yarn with a gram weight of 80 g / m 2 The inner fabric; Step 2: Add 61.1 g of dodecyl methacrylate, 51.2 g of glycidyl methacrylate, and 0.9 g of azobisisobutyronitrile to 60 g of 1,4-dioxane, and polymerize at 85° C. for 1.5 h in a nitrogen atmosphere. After the reaction is completed, filter the residue, wash it with 1,4-dioxane and ethanol four times respectively, and dry it to obtain a binary copolymer; The binary copolymer is added to 1,4-dioxane to obtain a hydrophobic finishing liquid with a mass fraction of 15%; the hydrophobic finishing liquid is atomized with an air compression atomizer, and then applied to one side of the inner layer fabric for 40 seconds, the resulting fabric is heated at 185°C for 3 minutes, then rinsed with 1,4-dioxane for 5 times, and dried to obtain a hydrophobic treated inner layer fabric; Step 3: 16.4 g of eugenol, 13.8 g of bis(2-mercaptoethyl) ether and 200 g of N,N-dimethylformamide were mixed and stirred at room temperature for 4.5 h. After the reaction was completed, the solvent was removed by rotary evaporation at 90° C. to obtain modified eugenol; 15 g of modified eugenol, 11.4 g of allyl glycidyl ether, and 120 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 7 h. After the reaction was completed, the solvent and excess allyl glycidyl ether were removed by rotary evaporation at 90° C. to obtain a modifier; At 65°C, 40 g of silk fibroin was added to 200 g of 9.3 mol / L lithium bromide aqueous solution, stirred for 80 min, and then 21 g of modifier was added, stirred and reacted at 65°C for 5.5 h. After the reaction, it was dialyzed for 7 days, during which distilled water was replaced 3 times a day. After the dialysis, the product was freeze-dried to obtain modified silk fibroin and stored at 4°C for future use. The modified silk fibroin and formic acid were mixed to obtain a spinning solution with a mass fraction of 15%, and then electrospinning was performed on the side of the hydrophobic treated inner layer fabric that was not hydrophobic treated to obtain the modified inner layer fabric; wherein, the electrospinning conditions were: an applied voltage of 14 kV, a receiving distance of 15 cm, a propulsion rate of -0.003 mm / s, an electrospinning needle of 22 G, a temperature of 35 ° C, and a humidity of 50%; Step 4: melt the polyester masterbatch and spin it at 290°C using a spinneret with a cross-shaped hole to obtain a shaped polyester fiber; spin the shaped polyester fiber into a yarn with a British count of 50, and knit it to obtain a yarn with a gram weight of 100g / m 2 Surface fabric; The surface fabric is immersed in a sodium hydroxide aqueous solution with a concentration of 200 g / L and a bath ratio of 1:60, and after being stirred and immersed at 85° C. for 20 minutes, it is taken out, washed, and dried to obtain a pretreated surface fabric; the pretreated surface fabric is immersed in a 3-mercaptopropyltriethoxysilane treatment solution with a bath ratio of 1:60, and after being stirred and immersed at room temperature for 40 minutes, it is taken out, washed, and dried to obtain a functionalized modified surface fabric; wherein the mass fraction of 3-mercaptopropyltriethoxysilane in the 3-mercaptopropyltriethoxysilane treatment solution is 6%, and the solvent is obtained by mixing ethanol and distilled water in a volume ratio of 4:1; The modified hydrophilic finishing agent is added to deionized water to obtain a hydrophilic finishing liquid, and the functionalized modified surface fabric is immersed in the hydrophilic finishing liquid with a bath ratio of 1:35. After being treated under ultraviolet light radiation, the fabric is taken out and pre-baked at 105°C for 2 minutes, and then baked at 165°C for 70 seconds to obtain a modified surface fabric; wherein, first, the amount of the modified hydrophilic finishing agent is 3% owf; the ultraviolet light radiation conditions are: ultraviolet light power 550W, irradiation distance 12cm, irradiation time 25min; The modified surface layer fabric is laminated with one side of the silk fibroin film in the modified inner layer fabric, and the layers are aligned and compounded to obtain a moisture-absorbing and quick-drying fabric. Example 5
[0021] This embodiment discloses a method for preparing a moisture-absorbing and quick-drying fabric, comprising the following steps: Step 1: Disperse 4.5 g of the composite nanomaterial in 150 g of toluene, perform ultrasonic treatment for 120 min, add 0.6 g of 3-aminopropyltriethoxysilane, reflux at 120° C. for 14 h, centrifuge, wash, and dry to obtain an amino composite nanomaterial; The cotton fiber was added to a sodium periodate aqueous solution with a concentration of 0.2 g / mL at a bath ratio of 1:45, and the mixture was kept at 35°C in a nitrogen atmosphere and protected from light for 2 h under stirring. The solid product was filtered and washed with ethanol and deionized water for 4 times each, and dried in vacuo at 38°C to obtain oxidized cotton fiber. The aminated composite nanomaterial was added to deionized water, ultrasonically treated for 30 minutes, and stirred for 1.5 hours to obtain a cotton fiber treatment solution with a concentration of 0.2 g / mL; the oxidized cotton fiber was added to the cotton fiber treatment solution at a bath ratio of 1:45, stirred for reaction at 50°C for 12 hours, and filtered, and the obtained solid product was washed with ethanol and deionized water for 4 times each, and vacuum dried at 38°C to obtain modified cotton fiber; The modified cotton fiber was spun into a yarn with a British count of 40, and knitted to obtain a yarn with a gram weight of 70 g / m 2 The inner fabric; Step 2: Add 45.8 g of dodecyl methacrylate, 39.3 g of glycidyl methacrylate, and 0.6 g of azobisisobutyronitrile to 50 g of 1,4-dioxane, and polymerize at 80° C. for 2 h in a nitrogen atmosphere. After the reaction is completed, filter the residue, wash it with 1,4-dioxane and ethanol three times respectively, and dry it to obtain a binary copolymer; The binary copolymer was added to 1,4-dioxane to obtain a hydrophobic finishing liquid with a mass fraction of 12.5%; the hydrophobic finishing liquid was atomized with an air compression atomizer, and then applied to one side of the inner layer fabric for 30 seconds, the obtained fabric was heated at 180°C for 5 minutes, and then rinsed with 1,4-dioxane for 4 times, and dried to obtain a hydrophobic treated inner layer fabric; Step 3: 12.3 g of eugenol, 10.4 g of bis(2-mercaptoethyl) ether, and 175 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 4 h. After the reaction was completed, the solvent was removed by rotary evaporation at 85° C. to obtain modified eugenol; 12.5 g of modified eugenol, 8.6 g of allyl glycidyl ether, and 110 g of N,N-dimethylformamide were mixed, and stirred for reaction at room temperature for 6 h. After the reaction was completed, the solvent and excess allyl glycidyl ether were removed by rotary evaporation at 85 ° C to obtain a modifier; At 60°C, 30g of silk fibroin was added to 175g of 9.3mol / L lithium bromide aqueous solution, stirred for 60min, and then 15g of modifier was added, stirred and reacted at 60°C for 6h. After the reaction, it was dialyzed for 6 days, during which distilled water was replaced 3 times a day. After the dialysis, the product was freeze-dried to obtain modified silk fibroin and stored at 4°C for future use. The modified silk fibroin and formic acid were mixed to obtain a spinning solution with a mass fraction of 14%, and then electrospinning was performed on the side of the hydrophobic treated inner layer fabric that was not hydrophobic treated to obtain the modified inner layer fabric; wherein, the electrospinning conditions were: an applied voltage of 13 kV, a receiving distance of 14 cm, a propulsion rate of 0.003 mm / s, an electrospinning needle of 22 G, a temperature of 30 ° C, and a humidity of 40%; Step 4: melt the polyester masterbatch and spin it at 280°C using a spinneret with a cross-shaped hole to obtain a shaped polyester fiber; spin the shaped polyester fiber into a yarn with a British count of 40, and knit it to obtain a yarn with a gram weight of 90g / m 2 Surface fabric; The surface fabric is immersed in a sodium hydroxide aqueous solution with a concentration of 200 g / L and a bath ratio of 1:50, and after being stirred and immersed at 80° C. for 30 minutes, it is taken out, washed, and dried to obtain a pretreated surface fabric; the pretreated surface fabric is immersed in a 3-mercaptopropyltriethoxysilane treatment solution with a bath ratio of 1:50, and after being stirred and immersed at room temperature for 30 minutes, it is taken out, washed, and dried to obtain a functionalized modified surface fabric; wherein the mass fraction of 3-mercaptopropyltriethoxysilane in the 3-mercaptopropyltriethoxysilane treatment solution is 5%, and the solvent is obtained by mixing ethanol and distilled water in a volume ratio of 4:1; The modified hydrophilic finishing agent is added to deionized water to obtain a hydrophilic finishing liquid, and the functionalized modified surface fabric is immersed in the hydrophilic finishing liquid with a bath ratio of 1:30. After being treated under ultraviolet light radiation, the fabric is taken out, pre-baked at 100°C for 3 minutes, and then baked at 160°C for 80 seconds to obtain a modified surface fabric; wherein, first, the amount of the modified hydrophilic finishing agent is 2% owf; the ultraviolet light radiation conditions are: ultraviolet light power 500W, irradiation distance 10cm, irradiation time 30min; The modified surface layer fabric is laminated with one side of the silk fibroin film in the modified inner layer fabric, and the layers are aligned and compounded to obtain a moisture-absorbing and quick-drying fabric.
[0022] The composite nanomaterial and modified hydrophilic finishing agent used in the above-mentioned Examples 3-5 are the composite nanomaterial prepared in Example 1 and the modified hydrophilic finishing agent prepared in Example 2. Comparative Example 1
[0023] Compared with Example 1, in the process of preparing the composite nanomaterial in Comparative Example 1, boron nitride nanorods are used instead of oxygen-doped boron nitride nanorods, and other conditions remain unchanged. Comparative Example 2
[0024] Compared with Example 1, in the process of preparing the composite nanomaterial, in Comparative Example 2, cuprous oxide / boron nitride nanomaterial is used instead of modified cuprous oxide / boron nitride nanomaterial, and other conditions remain unchanged. Comparative Example 3
[0025] Compared with Example 2, in the process of preparing the hydrophilic finishing agent in Comparative Example 3, no quaternary ammonium salt compound was added, and other conditions remained unchanged. Comparative Example 4
[0026] Compared with Example 5, in the process of preparing the modified cotton fiber in Comparative Example 4, the composite nanomaterial prepared in Comparative Example 1 was used, and other conditions remained unchanged. Comparative Example 5
[0027] Compared with Example 5, in the process of preparing the modified cotton fiber in Comparative Example 5, the composite nanomaterial prepared in Comparative Example 2 was used, and other conditions remained unchanged. Comparative Example 6
[0028] Compared with Example 5, in the process of preparing the modified cotton fiber in Comparative Example 6, the composite nanomaterial is replaced by the modified cuprous oxide / boron nitride nanomaterial, and other conditions remain unchanged. Comparative Example 7
[0029] Compared with Example 5, in the process of preparing the modified surface layer fabric in Comparative Example 7, the modified hydrophilic finishing agent prepared in Comparative Example 3 was used, and other conditions remained unchanged. Comparative Example 8
[0030] Compared with Example 5, in the process of preparing the moisture-absorbing and quick-drying fabric, Comparative Example 8 uses a hydrophobic treated inner layer fabric instead of the modified inner layer fabric, and other conditions remain unchanged. Comparative Example 9
[0031] Compared with Example 5, in the process of preparing the moisture-absorbing and quick-drying fabric in Comparative Example 9, the surface layer fabric is used instead of the modified surface layer fabric, and other conditions remain unchanged.
[0032] In the above embodiments and comparative examples, silk fibroin, CAS No. 96690-41-4, active ingredient content 99%, was provided by Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; polyester masterbatch, heat resistant temperature of 200-350°C, was provided by Dongguan Prius Plastic Raw Materials Co., Ltd.; polyethylene glycol 400, molecular weight 400, was provided by Shandong Baihua Chemical Co., Ltd. Experimental example
[0033] The performance of the moisture-absorbing and quick-drying fabrics prepared in Examples 3-5 and Comparative Examples 4-9 was tested.
[0034] 1. Antibacterial performance test: According to the international standard GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the test bacteria are Escherichia coli and Staphylococcus aureus.
[0035] 2. Hygroscopicity test: The water absorption rate is measured in accordance with the international standard GB / T21655.1-2008 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method" to characterize the hygroscopicity.
[0036] 3. Quick-drying performance test: Test the moisture permeability in accordance with the international standard GB / T12704-1991 to characterize the quick-drying performance.
[0037] 4. Instantaneous feeling value: It is measured in accordance with the international standard GB / T35263-2017 "Testing and evaluation of the instantaneous coolness of textiles upon contact".
[0038] The test results are shown in Table 1: ; It can be seen from the test results in Table 1 that the moisture-absorbing and quick-drying fabrics prepared in Examples 3-5 of the present invention have excellent moisture-absorbing and quick-drying performance, long-lasting antibacterial performance and good cool feeling.
[0039] From the comparison between comparative example 4 and example 5, it can be seen that hydroxyl groups are introduced on the surface of boron nitride nanorods by oxygen doping, so as to improve the interfacial compatibility between boron nitride nanorods and cotton fibers, and provide anchoring points for the growth of cuprous oxide, thereby affecting the antibacterial properties and cool feeling of the fabric; from the comparison between comparative example 5 and example 5, it can be seen that cuprous oxide is doped with chlorine, so that the band gap of the chlorine-doped nanocuprous oxide is reduced, and the visible light absorptivity is enhanced, so that the chlorine-doped nanocuprous oxide has better antibacterial ability under light conditions, thereby improving the antibacterial properties of the fabric; from the comparison between comparative example 6 and example 5, it can be seen that nano zinc oxide with antibacterial effect is grown on the surface of the modified cuprous oxide / boron nitride nanomaterial, and while synergistically antibacterial, the presence of nano zinc oxide can also prevent cuprous oxide from contacting with air, enhance the stability of cuprous oxide, and exert better antibacterial effect. Results; From the comparison between comparative example 7 and embodiment 5, it can be seen that after the modified hydrophilic finishing agent is used to treat the surface fabric, the hydrophilic and antibacterial quaternary ammonium salt compound structure in the modified hydrophilic finishing agent has a positive effect on the antibacterial property and the improvement of the moisture absorption and quick-drying property of the fabric; From the comparison between comparative example 8 and embodiment 5, it can be seen that the modified silk fibroin with antibacterial property is electrospinned to form a hydrophilic antibacterial silk fibroin film on the inner layer, the micropores and nanopores of the silk fibroin film are significantly smaller than those of the cotton fabric, and due to the hydrophobicity difference on both sides of the inner layer fabric, unidirectional moisture transport is achieved, which is conducive to the discharge of sweat and improves the perspiration quick-drying property and antibacterial property of the fabric; From the comparison between comparative example 9 and embodiment 5, it can be seen that the surface fabric is finished by the modified hydrophilic finishing agent, and the moisture absorption quick-drying property and antibacterial property of the surface fabric are improved.
[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a moisture-absorbing and quick-drying fabric, characterized in that: The following steps are involved: Step 1: treating the composite nanomaterial with 3-aminopropyltriethoxysilane to obtain an amino composite nanomaterial; oxidizing cotton fiber with sodium periodate to obtain oxidized cotton fiber, and depositing the amino composite nanomaterial on the oxidized cotton fiber to obtain modified cotton fiber; The modified cotton fiber is spun into yarn and knitted to obtain the inner layer fabric; Step 2: Copolymerizing dodecyl methacrylate and glycidyl methacrylate to obtain a binary copolymer, and applying the binary copolymer to one side of the inner layer fabric to obtain a hydrophobic treated inner layer fabric; Step 3, eugenol is modified by bis(2-mercaptoethyl) ether to obtain modified eugenol; Modified eugenol reacts with allyl glycidyl ether to obtain a modifier; the modifier is then used to modify silk fibroin to obtain modified silk fibroin; The modified silk fibroin is electrospinned to form a silk fibroin membrane on the side of the inner layer fabric that has not been hydrophobically treated, thereby obtaining a modified inner layer fabric; Step 4: melt spinning the polyester masterbatch to obtain shaped polyester fibers; spinning the shaped polyester fibers into yarns, knitting them, and obtaining surface fabrics; soaking the surface fabrics in a sodium hydroxide aqueous solution and a 3-mercaptopropyltriethoxysilane treatment solution to obtain functionalized modified surface fabrics; The functionalized modified surface layer fabric is treated with a hydrophilic finishing liquid containing a modified hydrophilic finishing agent to obtain a modified surface layer fabric; The modified surface layer fabric is laminated with one side of the silk fibroin film in the modified inner layer fabric, and the layers are aligned and compounded to obtain a moisture-absorbing and quick-drying fabric.
2. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In step 1, the weight of the inner layer fabric is 60-80g / m 2 ; The British count of yarn spun from modified cotton fiber is 30-50.
3. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In the step 1, the method for preparing the composite nanomaterial comprises the following steps: Step A1, adding boric acid to deionized water, and stirring at 40-50°C for 10-30 minutes, then adding 0.02g / mL melamine aqueous dispersion, stirring and reacting at 40-50°C for 5.5-6.5h, and drying the reaction mixture at 65-75°C to obtain a boron nitride precursor; sintering the boron nitride precursor at 1000-1200°C for 100-150min in a nitrogen atmosphere to obtain boron nitride nanorods; wherein the mass ratio of boric acid, deionized water, and melamine aqueous dispersion is (3.7-7.4):(40-80):(60-120); Adding boron nitride nanorods to a sodium hydroxide aqueous solution with a concentration of 5 mol / L, stirring at 75-85° C. for 5.5-6.5 hours, centrifuging, washing, and drying to obtain oxygen-doped boron nitride nanorods; wherein the amount ratio of the boron nitride nanorods to the sodium hydroxide aqueous solution is (1-2) g: (250-500) mL; Step A2, adding oxygen-doped boron nitride nanorods and copper nitrate into deionized water, ultrasonically dispersing for 20-40 minutes, then stirring at room temperature for 1-2 hours, adding hydrazine hydrate, precipitating for 1-2 hours, filtering, washing, and drying to obtain cuprous oxide / boron nitride nanomaterials; wherein the mass ratio of oxygen-doped boron nitride nanorods, copper nitrate, deionized water, and hydrazine hydrate is (4-5):(1.7-3.4):(80-100):(1.1-1.9); The cuprous oxide / boron nitride nanomaterial is mixed with sodium chloride in a mass ratio of (3-5):(0.5-0.9), ground at room temperature for 10-20 minutes, washed with water for 3-5 times, and dried to obtain a modified cuprous oxide / boron nitride nanomaterial; The modified cuprous oxide / boron nitride nanomaterial is mixed with a 0.5 mol / L zinc chloride aqueous solution at a dosage ratio of (0.6-1.2) g: (100-300) mL, subjected to ultrasonic microwave reaction for 100-150 min, filtered, washed and dried to obtain a composite nanomaterial.
4. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In the step 1, the preparation method of the modified cotton fiber is: The composite nanomaterial is dispersed in toluene, subjected to ultrasonic treatment for 100-150 minutes, and then 3-aminopropyltriethoxysilane is added, and refluxed at 110-130° C. for 12-16 hours, and purified to obtain an amino composite nanomaterial; wherein the mass ratio of the composite nanomaterial, toluene, and 3-aminopropyltriethoxysilane is (3-6):(100-200):(0.3-0.9); The cotton fiber is added to a sodium periodate aqueous solution with a concentration of 0.2 g / mL, with a bath ratio of 1:(40-50), and the mixture is stirred in a nitrogen atmosphere at a temperature of 33-37° C. and oxidized for 1.5-2.5 hours in the dark, filtered, washed, and dried to obtain oxidized cotton fiber; The amino composite nanomaterial is added into deionized water, ultrasonically treated for 20-40 minutes, and then stirred for 1-2 hours to obtain a cotton fiber treatment solution with a concentration of 0.1-0.3 g / mL; the oxidized cotton fiber is added into the above cotton fiber treatment solution with a bath ratio of 1:(40-50), stirred and reacted at 45-55°C for 10-15 hours, filtered, washed, and dried to obtain modified cotton fiber.
5. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In the step 2, the preparation method of the hydrophobic treated inner layer fabric is: Add dodecyl methacrylate, glycidyl methacrylate and azobisisobutyronitrile to 1,4-dioxane, and carry out polymerization reaction at 75-85°C for 1.5-2.5 hours in a nitrogen atmosphere. After the reaction, filter, wash and dry to obtain a binary copolymer; wherein the mass ratio of dodecyl methacrylate, glycidyl methacrylate, azobisisobutyronitrile and 1,4-dioxane is (30.5-61.1):(27.3-51.2):(0.3-0.9):(40-60); The binary copolymer is added to 1,4-dioxane to obtain a hydrophobic finishing liquid with a mass fraction of 10-15%; the hydrophobic finishing liquid is atomized and then applied to one side of the inner layer fabric for 20-40 seconds, the resulting fabric is heated at 175-185°C for 3-8 minutes, then rinsed with 1,4-dioxane for 3-5 times, and dried to obtain a hydrophobic treated inner layer fabric.
6. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In step 3, the preparation method of the modified inner layer fabric is: Mix eugenol, bis(2-mercaptoethyl) ether and N,N-dimethylformamide, stir and react at room temperature for 3.5-4.5 hours, and after the reaction, rotary evaporate to obtain modified eugenol; wherein the mass ratio of eugenol, bis(2-mercaptoethyl) ether and N,N-dimethylformamide is (8.2-16.4):(6.9-13.8):(150-200); Modified eugenol, allyl glycidyl ether and N,N-dimethylformamide are mixed, stirred and reacted at room temperature for 5-7 hours, and after the reaction is completed, rotary evaporation is performed to obtain a modifier; wherein the mass ratio of modified eugenol, allyl glycidyl ether and N,N-dimethylformamide is (10-15):(5.7-11.4):(100-120); At 55-65° C., add silk fibroin to a 9.3 mol / L lithium bromide aqueous solution, stir for 40-80 min, then add a modifier, stir and react at 55-65° C. for 5.5-6.5 h, dialyze for 5-7 days after the reaction, replace distilled water 3 times a day during the dialysis period, freeze-dry the product after the dialysis to obtain modified silk fibroin and store at 4° C. for standby use; wherein the mass ratio of silk fibroin, lithium bromide aqueous solution and modifier is (20-40):(150-200):(9-21); The modified silk fibroin and formic acid are mixed to obtain a spinning solution with a mass fraction of 13-15%, and then electrospinning is performed on the side of the hydrophobic treated inner layer fabric that has not been hydrophobic treated to obtain a modified inner layer fabric; wherein, the electrospinning conditions are: an applied voltage of 12-14 kV, a receiving distance of 13-15 cm, a propulsion rate of 0.0020-0.003 mm / s, an electrospinning needle of 21-22 G, a temperature of 25-35 ° C, and a humidity of 30-50%.
7. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In the step 4, the spinning temperature of the polyester masterbatch is 270-290°C; the British count of the yarn spun from the shaped polyester fiber is 30-50; the gram weight of the surface fabric is 80-100g / m 2 .
8. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In the step 4, the preparation method of the modified surface layer fabric is: The surface fabric is immersed in a sodium hydroxide aqueous solution with a concentration of 200 g / L, with a bath ratio of 1:(40-60), and the surface fabric is taken out after being stirred and immersed at 75-85° C. for 20-40 minutes, washed, and dried to obtain a pretreated surface fabric; The pretreated surface fabric is immersed in a 3-mercaptopropyl triethoxysilane treatment solution at a bath ratio of 1:(40-60), and after being stirred and immersed for 20-40 minutes at room temperature, it is taken out, washed, and dried to obtain a functionalized modified surface fabric; wherein the mass fraction of 3-mercaptopropyl triethoxysilane in the 3-mercaptopropyl triethoxysilane treatment solution is 4-6%, and the solvent is obtained by mixing ethanol and distilled water at a volume ratio of 4:1; Add a modified hydrophilic finishing agent into deionized water to obtain a hydrophilic finishing liquid, immerse the functionalized modified surface fabric in the hydrophilic finishing liquid at a bath ratio of 1:(25-35), take out after treatment under ultraviolet light radiation, pre-bake at 95-105°C for 2-4 minutes, and then bake at 155-165°C for 70-90 seconds to obtain a modified surface fabric; wherein the amount of the modified hydrophilic finishing agent is 1-3% owf; ultraviolet light radiation conditions: ultraviolet light power 450-550W, irradiation distance 8-12cm, irradiation time 25-35min.
9. The method for preparing the moisture-absorbing and quick-drying fabric according to claim 1, characterized in that: In the step 4, the preparation method of the modified hydrophilic finishing agent is: Step B1, 2-mercapto-1,4-phthalic acid, ethylene glycol, p-toluenesulfonic acid and N,N-dimethylformamide are mixed, heated to 120-130° C. in a nitrogen atmosphere, stirred and reacted for 4-5 hours, and after the reaction is completed, purified to obtain an intermediate product; wherein the mass ratio of 2-mercapto-1,4-phthalic acid, ethylene glycol, p-toluenesulfonic acid and N,N-dimethylformamide is (9.9-19.8):(3.1-6.2):(0.5-0.9):(100-120); The intermediate product, 2-acrylamide-2-methylpropane sulfone and deionized water are mixed, stirred and reacted at room temperature for 5-7 hours. After the reaction is completed, the solvent is evaporated to obtain a hydrophilic compound; wherein the mass ratio of the intermediate product, 2-acrylamide-2-methylpropane sulfone and deionized water is (2.9-5.8):(2.1-4.2):(100-120); Dissolve triethanolamine in N,N-dimethylformamide, and add 1-bromobutane dropwise, heat to 65-75°C, stir and react for 11-13h, and rotary evaporate to obtain a quaternary ammonium salt compound; wherein the mass ratio of triethanolamine, 1-bromobutane and N,N-dimethylformamide is (7.5-15):(8.2-16.4):(30-50); A hydrophilic compound, a quaternary ammonium salt compound, polyethylene glycol 400, and antimony trioxide are mixed, heated to 200-240° C. in a nitrogen atmosphere, the temperature is kept constant and the pressure is reduced to 0.001-0.02 MPa, and the reaction is continued for 2.5-5 hours to obtain a hydrophilic finishing agent; wherein the mass ratio of the hydrophilic compound, the quaternary ammonium salt compound, polyethylene glycol 400, and antimony trioxide is (3.6-8.6):(10-20):(6.5-13):(0.1-0.3); Step B2, mix a hydrophilic finishing agent, isocyanoethyl methacrylate, and N,N-dimethylformamide, add dibutyltin dilaurate, stir and react at 75-85°C for 4.5-5.5h, and rotary evaporate to obtain a modified hydrophilic finishing agent; wherein the mass ratio of the hydrophilic finishing agent, isocyanoethyl methacrylate, N,N-dimethylformamide, and dibutyltin dilaurate is (10.1-20.8):(7.8-15.6):(150-200):(0.08-0.15).
10. A moisture-absorbing and quick-drying fabric prepared by the method for preparing a moisture-absorbing and quick-drying fabric as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Moisture-absorbing and quick-drying polyester fiber and fabric
CN118048708B
Cited By
Biomass multi-layer fabric, preparation method and clothes made of biomass multi-layer fabric
CN120716246A
A biomass multilayer fabric, its preparation method, and clothing made from the fabric.
CN120716246B